A quantitative priority-based approach using a multi-criteria decision-making model for sustainable coastal city development - Gokkaya, Merve Dilman; Demir, Sara; Aksoy, Onur; Ersoz, Nazli Deniz (Springer, 2025)
Throughout history, water availability has been an essential factor in shaping the development, culture, transportation, economic activities, and access to food in cities. The socioeconomic and cultural development of a city or country with a coast depends on the active use of the coast and the impact of the coast on urban life. In this context, for the development of coastal cities, it is necessary to determine coastal city criteria and specify their strategies in line with these criteria in order to increase coastal qualities. This research determined Bursa, located northwest of Turkey, as the study area. However, factors such as the absence of a coastal plan for the city and the inability of the coast to integrate into urban life have weakened the coastal city's qualities of it. For this reason, this study aims to define Bursa's coastal city criteria and determine strategies to increase the coastal city quality. The coastal city criteria developed depending on the examples of coastal cities in the world were evaluated by surveying local people and experts. The results of these surveys were digitized according to their priorities using Analytical Hierarchical Process (AHP), one of the multi-criteria decision-making (MCDM) methods. The results of this study determined the highest priority criteria among the three main and nine sub-coastal city criteria in evaluating the coastal city in Bursa. This study proposes a numerical method that develops effective and sustainable coastal design and planning strategies for Turkey and underdeveloped countries.
Keywords: Coastal cities; Coastal criteria; Multiple-criteria decision-making (MCDM) method; Analytic hierarchy process (AHP); Turkey; Bursa